Efficacy and safety of pembrolizumab in advanced gastric and gastroesophageal junction cancer: a systematic review and meta-analysis - Xiaoying Ji; Guoping Wang; Dandan Pan; Shanxia Xu; Xinming Lei (BMC Gastroenterology)
Abstract Background Pembrolizumab, a PD-1 inhibitor, has shown potential for treating advanced gastric and gastroesophageal junction (GEJ) cancer. This meta-analysis evaluates its efficacy and safety, alone or combined with chemotherapy, in this population. Methods A systematic review and meta-analysis were conducted in accordance with PRISMA guidelines. Databases including PubMed, Embase, the Cochrane Central Register of Controlled Trials, and Web of Science were searched up to October 31, 2024. Twelve studies comprising 4,069 patients were included. The primary outcomes were overall survival (OS) and progression-free survival (PFS); secondary outcomes included objective response rate (ORR), adverse events (AEs), and grade ≥ 3 AEs. Effect sizes were calculated using mean differences (MDs) and odds ratios (ORs) with 95% confidence intervals (CIs). Results Pembrolizumab combined with chemotherapy significantly improved OS (MD = 1.92 months; 95% CI: 0.94 to 2.91) and ORR (MD = 11.05%; 95% CI: 6.29 to 15.82) compared to chemotherapy alone. Pembrolizumab monotherapy did not show a significant effect on OS (MD = 0.24 months; 95% CI: –1.15 to 1.63) and was associated with a significant reduction in PFS (MD = –2.28 months; 95% CI: –2.85 to –1.71) compared to chemotherapy alone. For safety, pembrolizumab monotherapy significantly reduced the risk of AEs (OR = 0.68; 95% CI: 0.57 to 0.81) and grade ≥ 3 AEs (OR = 0.39; 95% CI: 0.30 to 0.51) compared to chemotherapy. Pembrolizumab combined with chemotherapy did not significantly alter the risk of AEs (OR = 1.01; 95% CI: 0.90 to 1.13) or grade ≥ 3 AEs (OR = 1.12; 95% CI: 0.99 to 1.27) compared to chemotherapy alone. Conclusion Pembrolizumab combined with chemotherapy improves survival and response rates with a manageable safety profile in advanced gastric and GEJ cancers. Monotherapy shows limited efficacy, highlighting the need for combination strategies and patient selection.